2015
DOI: 10.1111/nph.13454
|View full text |Cite
|
Sign up to set email alerts
|

Phytase activity in lichens

Abstract: Summary Phytase activity was investigated in 13 lichen species using a novel assay method. The work tested the hypothesis that phytase is a component of the suite of surface‐bound lichen enzymes that hydrolyse simple organic forms of phosphorus (P) and nitrogen (N) deposited onto the thallus surface.Hydrolysis of inositol hexaphosphate (InsP6, the substrate for phytase) and appearance of lower‐order inositol phosphates (InsP5–InsP1), the hydrolysis products, were measured by ion chromatography. Phytase activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…Phytate is accumulated by plants ( Balaban et al, 2016 ), and to a lesser extent by microorganisms ( Turner et al, 2021 ), as a P storage compound. The capacity to hydrolyse phytate has been reported as widespread among lichens, which potentially contributes to P capture from atmospheric deposits and plant leachates ( Higgins and Crittenden, 2015 ). Phosphonates, on the other hand, can be found in membranes or excretions of microorganisms ( Horsman and Zechel, 2017 ; Calcott et al, 2018 ) and groups of phosphonate biosynthetic genes have been reported in lichenized Nostoc ( Gagunashvili and Andrésson, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytate is accumulated by plants ( Balaban et al, 2016 ), and to a lesser extent by microorganisms ( Turner et al, 2021 ), as a P storage compound. The capacity to hydrolyse phytate has been reported as widespread among lichens, which potentially contributes to P capture from atmospheric deposits and plant leachates ( Higgins and Crittenden, 2015 ). Phosphonates, on the other hand, can be found in membranes or excretions of microorganisms ( Horsman and Zechel, 2017 ; Calcott et al, 2018 ) and groups of phosphonate biosynthetic genes have been reported in lichenized Nostoc ( Gagunashvili and Andrésson, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, despite the lower abundance of organic phosphate solubilizers in comparison to mineral phosphate solubilizers, the former could play an essential role in recycling the old parts of the thallus ( Grube et al, 2015 ), releasing phosphate that members of the lichen symbiosis could use. It is important to highlight that phosphatase and phytase activity have been reported in several species of lichens ( Whiteford et al, 2010 ; Higgins and Crittenden, 2015 ), attributed to lichen enzymes being produced by the mycobiont. However, the primers chosen for this study were designed to amplify bacterial genes ( Bergkemper et al, 2016a ), which would indicate that the lichen microbiome is at least contributing to P turnover.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, N limitation could impede the process of P solubilization. Thus, for example, a N effect has been demonstrated on phytase activities in lichens [70]. Authors have shown a decrease in phytase activity along with the N availability in these complex microorganisms, for which phytate degradation is generally attributed to the fungal part of lichens.…”
Section: N Availability As a Key Factor Of Success Of Plant-psb Assoc...mentioning
confidence: 99%
“…The increasing mined phosphate prices demand alternative phosphate sources and the efficient phosphate utilization technology around the world (Brinch-Pedersen et al 2014). Phytin is a mixed salt (K + , Ca 2+ , Mg 2+ or Zn 2+ ) with phytate, account for up to 85% of total organic phosphorus in seeds and straws (Higgins and Crittenden 2015). High levels of unutilized phytate lead to phosphorus runoff from oversupplied agricultural soils to aquatic ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Phytase was viewed as a tool for determining the phytin degradation and phosphorus bioavailability (Brinch-Pedersen et al 2014). It can be produced most notably in germinating seeds and microbes (Nasri et al 2011;Higgins and Crittenden 2015). However, the mature plant and monogastric animals have only limited phytase activity in their nutrition absorption organs.…”
Section: Introductionmentioning
confidence: 99%